THE IMPACT OF DIGITAL MARKETING AND BRAND TRUST ON ONLINE PURCHASE DECISIONS: A STUDY OF IFIVE PERFUME CUSTOMERS - Sutariyono; Tohiroh (JURNAL ASIK, 2025)
This study aims to determine the effect of digital marketing and brand trust on online purcasing decisions among Ifive Perfume customers. The underlying problem is the importance of effective human resource management through fair digital marketing and a transparent, merit-based promotion system to improve online purcasing decisions. The method used in this study was quantitative. Data were collected through questionnaires distributed to 50 respondents, who were online customers of IFive Perfume. Data analysis techniques included simple and multiple linear regression analysis, t-tests, F-tests, and coefficients of determination using SPSS. The results showed that digital marketing had a partial positive and significant effect on online purcasing decisions, with a calculated t-value of 9.073 > t-table 2.012 and a significance level of 0.000. Similarly, brand trust also had a positive and significant effect on online purchasing decisons, with a calculated t-value of 10.492 > ttable 2.012 and a significance level of 0.000. Simultaneously, digital marketing and brand trust significantly influence online purcasing decisions, as indicated by the calculated F-value of 69.673 > F-table 3.20, with a significance level of 0.000. The Rsquare value of 0.748 indicates that 74.8% of the variation in online purcasing decisions can be explained by digital marketing and brand trust.